2005
DOI: 10.2741/1584
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERK1/2 IN FSH-induced PCNA expression and steroidogenesis in granulosa cells

Abstract: Follicular development is characterized by both proliferation and differentiation of granulosa cells (GCs) under the control of FSH. However, the cellular mechanism by FSH is not known. Using cultured GCs, we examined whether FSH activated ERK1/2 was involved in the regulation of the proliferation related gene proliferating cell nuclear antigen (PCNA) and steroidogenesis. GCs were obtained from the ovaries of DES treated immature rats and cultured in serum free medium. The results showed that FSH activated ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…In the present study, we found that in both cultured preovulatory GCs and immature female rats, the treatment of arsenite increased progesterone production which is an indicator of GC differentiation (Yu et al, 2005). Previous studies have reported that arsenic contributes to differentiation in leukemia cells (Nayak et al, 2010;Noh et al, 2010).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…In the present study, we found that in both cultured preovulatory GCs and immature female rats, the treatment of arsenite increased progesterone production which is an indicator of GC differentiation (Yu et al, 2005). Previous studies have reported that arsenic contributes to differentiation in leukemia cells (Nayak et al, 2010;Noh et al, 2010).…”
supporting
confidence: 55%
“…Yu et al (2005) demonstrated that steroidogenesis is a marker of GCs differentiation. Caspase-3 is required for the differentiation of skeletal muscle, embryonic Fig.…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK3/1-dependent pathway also has been reported as being involved in the regulation of steroidogenesis in granulosa cells; however, its precise role in this process is controversial. Some studies suggest that activation of MAPK is required for promoting steroidogenesis and steroidogenic gene expression in granulosa cells [36][37][38][39][40][41][42], whereas other studies indicate that activation of MAPK3/1 suppresses granulosa cell steroidogenesis and steroidogenic gene expression [38,[43][44][45]. Notably, most of the previous studies use either human luteinizing granulosa cells derived from patients receiving in vitro fertilization treatment or rat granulosa cells isolated from early antral follicles.…”
Section: Introductionmentioning
confidence: 94%
“…Endothelial PAS-domain protein 1 (EPAS1) is phosphorylated by p44/42 MAP kinase pathway, and is also involved in angiogenesis of human renal carcinoma (Conrad et al, 1999). Proliferating cell nuclear antigen (PCNA) has a pivotal role in the regulation of cell growth, acts as a prognostic factor of metastasis in breast cancer and is a substrate of p44/42 MAP kinase (Yu et al, 2005). The level of PCNA correlates directly with the rates of cellular proliferation and DNA synthesis (Prosperi, 1997).…”
Section: Discussionmentioning
confidence: 99%